PARENTAL BELIEFS ABOUT THEIR CHILDREN’S EXPRESSION OF NEGATIVE EMOTIONS: REEXAMINING THE FACTORIAL STRUCTURE OF TWO MEASURES AND THEIR DISCRIMINANT VALIDITY - Carona, Carlos; Moreira, Helena; Fonseca, Ana (International Journal of Child, Youth and Family Studies, 2022)
The Display of Negative Emotions scale and The Social Consequences Of Negative Emotions scale are two understudied questionnaires that assess parents’ emotion beliefs about their children’s expression of negative emotions. Therefore, the aims of this study were to ascertain the factorial structure of both questionnaires, to reexamine the internal consistency of each instrument’s scales, and to assess the age- and gender-related discriminant validity of the measures. The two questionnaires were administered by a web-based survey to a sample of 253 Portuguese mothers with children of elementary school age (6–12 years). A two-factor solution (expression of submissive emotions, expression of dominant emotions) was preferred for the first questionnaire, and a single-factor solution emerged for the second questionnaire. Both measures revealed good internal consistency, but while the former was able to identify gender differences, the latter discriminated between age groups. The simultaneous use of these questionnaires is recommended for an informative assessment of parents’ beliefs about their children’s expression of negative emotions.